Constituents and Characteristics of Hybrid Businesses: A Qualitative, Empirical Framework. (1st October 2016) - Hahn, Rüdiger; Ince, Inan
Abstract : Despite mounting research on hybrid businesses that deliver value beyond financial goals, little is known about their nature. We assess what characterizes hybrid businesses and drives their founders by means of an abductive analysis of 18 ventures. Findings are discussed for the outcome of business models, organization of business model, and underlying aims of hybrid entrepreneurs building an empirical framework of constituents and characteristics. Results show participatory patterns of organization and emphasis on knowledge sharing about sustainability. The general profit and growth orientation is often a means to the end of achieving sustainability goals. Entrepreneurs are driven by nonmaterial motives.